Monosialitization as the main chemical weathering process in the Poços de Caldas alkaline plateau (MG) - de Mello, Rafael Carvalho Alves [UNESP]; da Conceição, Fabiano Tomazini [UNESP]; Fernandes, Alexandre Martins [UNESP]; de Souza Sardinha, Diego (Revista Brasileira de Geomorfologia, 2022)
The characteristics of surface waters are strongly influenced by chemical weathering processes of the rocks in a watershed. Thus, this work investigated the chemical weathering influences on the surface water composition in the Poços de Caldas alkaline plateau, studying the Ariranha Stream basin. The physical and chemical parameters were evaluated monthly, totalizing twelve samples throughout 2016. The results indicated that the Ariranha Stream waters are constituted mainly by HCO3- and Na+ dissolved ions. The dissolved load was 247,6 t/a in 2016, with the majority being transported in the wet period (75,6%). The annual flux of 25,3 t/km2/a is lower than the obtained in other watersheds composed for alkaline rocks in Brazil or elsewhere, independently of the climatic conditions. The Ariranha Stream waters are controlled by a mixed between the rainwaters and the monossialitisation processes of the primary minerals of the Poços de Caldas alkaline plateau.
Monossialitização como principal processo de intemperismo químico no planalto alcalino de Poços de Caldas (MG)
Keywords: Alkaline rocks; Chemical erosion; Water-rock interactions